Legal aspects of cooperation between local authorities of Ukraine and European municipalities - Klyuyeva, Y.N. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article examines the legal aspects of the legal regulation of cooperation between local self-government bodies (territorial communities) of Ukraine and territorial communities of foreign countries — subjects of cross-border cooperation. Several aspects of the essence of cooperation of territorial communities with municipalities of European countries and among themselves are revealed. It has been established that local self-government bodies carry out their activities in accordance with and within the limits of current legislation, both national and international treaties. Basic international legal acts and legal acts of Ukraine regulating the process of functioning of local self-government bodies, in particular in the field of cooperation, define the list of functions and powers exercised by such bodies themselves and independently, determine the role and place of territorial communities in the development of cross-border cooperation. Mechanisms and forms of community cooperation were analyzed, as well as recommendations were given for improving legal regulation. The article is devoted to the analysis of current legislation in the field of community cooperation, as well as prospects for its improvement.
Правовые аспекты сотрудничества органов местного самоуправления Украины с европейскими муниципалитетами
Украинаның жергілікті өзін-өзі басқару органдарының еуропалық муниципалитеттермен ынтымақтастығының құқықтық аспектілері
Keywords: community cooperation; forms of community cooperation; cross-border cooperation; Euroregions; projects